Charting the Course: Total Factor Productivity Trends in Croatia Post-pre-bankruptcy Act - Šergo, Zdravko; Gržinić, Jasmina; Sučić Červa Mirela (LeXonomica, 2023)
The synthetic control method (SCM) is a valuable tool for unbiased pre-bankruptcy reform analysis in economic policy evaluations. This study utilizes SCM to assess the impact of the Financial Operations and Pre-Bankruptcy Settlement Act (AFOPBS) on Croatia’s total factor productivity (TFP). Control units and weights were meticulously chosen to construct a synthetic control for Croatia, creating a counterfactual scenario for the reform’s absence. The policy’s impact was quantified by comparing TFP growth post-policy between Croatia and its synthetic control. Placebo tests confirmed the results’ significance, and further validation was achieved through panel difference-in-differences analysis (PDID). Our findings show that the pre-bankruptcy reform in late 2012 effectively reduced the gap between Croatia and its synthetic control throughout the post-treatment years. However, it had two short-term adverse impacts and a subsequent recovery-like phase. These effects were statistically significant and confirmed by cross-validation. In conclusion, Croatia’s pre-bankruptcy reform significantly influenced TFP volatility, highlighting SCM’s effectiveness in evaluating economic policies, especially those crucial for economic growth Povzetek Metoda sintetične kontrole (SCM) je dragoceno orodje za nepristransko analizo reforme pred stečajem pri vrednotenju ekonomskih politik. Ta študija uporablja SCM za oceno vpliva Zakona o finančnem poslovanju in predstečajni poravnavi (AFOPBS) na skupno faktorsko produktivnost (TFP) na Hrvaškem. Kontrolne enote in uteži so bile skrbno izbrane za oblikovanje sintetične kontrole za Hrvaško, s čimer je bil ustvarjen nasprotni scenarij za odsotnost reforme. Vpliv politike je bil količinsko opredeljen s primerjavo rasti skupne faktorske produktivnosti po uvedbi politike med Hrvaško in njeno sintetično kontrolo. Placebo testi so potrdili pomembnost rezultatov, nadaljnja potrditev pa je bila dosežena s panelno analizo razlik v razlikah (PDID). Naše ugotovitve kažejo, da je reforma pred stečajem konec leta 2012 učinkovito zmanjšala razliko med Hrvaško in njeno sintetično kontrolo v vseh letih po izvedbi ukrepa. Vendar je imela dva kratkoročna negativna učinka in poznejšo fazo, podobno okrevanju. Ti učinki so bili statistično značilni in potrjeni z navzkrižnim preverjanjem. Zaključimo lahko, da je hrvaška reforma pred stečajem pomembno vplivala na nestanovitnost skupne faktorske produktivnosti, kar poudarja učinkovitost SCM pri ocenjevanju gospodarskih politik, zlasti tistih, ki so ključne za gospodarsko rast